Mr.Y Design / Muhammad Yamin Abd Rahman - Muhammad Yamin Abd Rahman, Abd Rahman (2020)
A simple design yet looks artistic is important to be on a packaging to enhance a business sale by the attractive packaging. The concept applied in Mr.Y Design company is to improvise the uninspired-, dull-looking and eyesore design which happens to be on most local packaging by bringing both affordable price and attractive design to the customers. Apart from that, an attractive packaging signifies an identity of a product.